Pengaruh Fundamental Makro Terhadap Sustainability Disclousure dengan Kinerja Keuangan, Karakteristik Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - Ricky Zakaria Winarno; Hwihanus Hwihanus (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This study aims to explore the impact of macroeconomic fundamentals on sustainability disclosure in mining companies listed on the Indonesia Stock Exchange. The research utilizes financial performance, company attributes, and ownership structure as linking variables. The approach used is quantitative, employing secondary data from financial statements and sustainability reports of the companies. The population under investigation includes all mining companies registered on the Indonesia Stock Exchange from 2019 to 2022. The data analysis methods applied include path analysis and regression to examine the relationships between the various factors. It is hoped that the findings of this study will provide deeper insights into the factors influencing sustainability disclosure in the mining sector and offer relevant policy implications for companies and regulators in Indonesia.